(8k+7)(k+1)=9

Simple and best practice solution for (8k+7)(k+1)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8k+7)(k+1)=9 equation:


Simplifying
(8k + 7)(k + 1) = 9

Reorder the terms:
(7 + 8k)(k + 1) = 9

Reorder the terms:
(7 + 8k)(1 + k) = 9

Multiply (7 + 8k) * (1 + k)
(7(1 + k) + 8k * (1 + k)) = 9
((1 * 7 + k * 7) + 8k * (1 + k)) = 9
((7 + 7k) + 8k * (1 + k)) = 9
(7 + 7k + (1 * 8k + k * 8k)) = 9
(7 + 7k + (8k + 8k2)) = 9

Combine like terms: 7k + 8k = 15k
(7 + 15k + 8k2) = 9

Solving
7 + 15k + 8k2 = 9

Solving for variable 'k'.

Reorder the terms:
7 + -9 + 15k + 8k2 = 9 + -9

Combine like terms: 7 + -9 = -2
-2 + 15k + 8k2 = 9 + -9

Combine like terms: 9 + -9 = 0
-2 + 15k + 8k2 = 0

Factor a trinomial.
(-2 + -1k)(1 + -8k) = 0

Subproblem 1

Set the factor '(-2 + -1k)' equal to zero and attempt to solve: Simplifying -2 + -1k = 0 Solving -2 + -1k = 0 Move all terms containing k to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1k = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1k = 0 + 2 -1k = 0 + 2 Combine like terms: 0 + 2 = 2 -1k = 2 Divide each side by '-1'. k = -2 Simplifying k = -2

Subproblem 2

Set the factor '(1 + -8k)' equal to zero and attempt to solve: Simplifying 1 + -8k = 0 Solving 1 + -8k = 0 Move all terms containing k to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -8k = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -8k = 0 + -1 -8k = 0 + -1 Combine like terms: 0 + -1 = -1 -8k = -1 Divide each side by '-8'. k = 0.125 Simplifying k = 0.125

Solution

k = {-2, 0.125}

See similar equations:

| (2)-(-b)=6 | | 118=-8+7(8-2x) | | (-8)+x=-3 | | 2w^2+3w=324 | | P(p-3)-6p-18=0 | | 7y(3x+2y)= | | 8/14x=6/10 | | 8/14=6/10 | | 28y-187=15x | | 5/9x=60 | | 7p^2-12p-2=5p-8 | | -2x+8=3x+10 | | 63=6n+3n-2n | | 15y+187=28x | | 6h^2+26h-2=-10 | | 0.36*(11/2) | | x^5+540=0 | | 2.5x+2.8=-1.2x+9.8 | | F(x)=8-2x-x^2 | | (x+6)=2(1-x) | | 2.3x+2.8=-1.3x+9.8 | | 4m+5m-9=3m+m+6 | | 6k^2+k-12=0 | | 4x-3/5x÷4x^2-5/5 | | x^5-x^4-x^3+x^2-2x+2=0 | | 2.5x=11+3x | | X^2-9x-56=0 | | r/2-r/3=3 | | cot^2(x)=3 | | 25/4=R/5 | | 4y^2=400 | | .1*.56*x+.5x=48000 |

Equations solver categories